2008
DOI: 10.1158/0008-5472.can-07-5580
|View full text |Cite
|
Sign up to set email alerts
|

Cells Silenced forSDHBExpression Display Characteristic Features of the Tumor Phenotype

Abstract: Recently, enzymes of the tricarboxylic acid (TCA) cycle have emerged as novel tumor suppressors. In particular, mutations in the nuclear-encoded subunits of succinate dehydrogenase (SDHB, SDHC, and SDHD) cause paragangliomas and pheochromocytomas. Although the mechanism(s) by which disruption of mitochondrial metabolism leads to neoplasia is largely unknown, increasing evidence points to an activation of pseudohypoxia. In this study, we have shown that silencing of SDHB using DNA-based small interfering RNA re… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
79
2

Year Published

2009
2009
2014
2014

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 88 publications
(87 citation statements)
references
References 48 publications
6
79
2
Order By: Relevance
“…Both reagents target the SDHA succinate-binding site and equally inhibit the SDH and SQR activities (Brusque et al, 2002;Lemarie et al, 2011). When the tumour-suppressor gene function of complex II subunits was discovered for SDHD, SDHC and SDHB (Baysal et al, 2000;Niemann and Muller, 2000;Astuti et al, 2001), two mechanisms were evoked to explain the oncogenesis process associated with complex II deficiency: (1) the establishment of a pseudo-hypoxic state leading to HIF1a stabilization in tumours through succinate inhibition of the HIF1a prolyl hydroxylase (PHD), which favours the glycolytic pathway and promotes tumour formation (GimenezRoqueplo et al, 2001;Pollard et al, 2005Pollard et al, , 2006Selak et al, 2005;Lehtonen et al, 2007;Cervera et al, 2008) and (2) the long-term generation of sublethal superoxides at the complex II level contributing to either genomic instability and subsequent tumoral development or HIF1a stabilization (Senoo-Matsuda et al, 2001;Ishii et al, 2005;Slane et al, 2006;Guzy et al, 2008). Various key publications subsequently brought to light the possible role of complex II as a proapoptotic sensor, through the production of deleterious high levels of ROS, which could provide a third explanation as to why complex II subunits are disabled in tumourigenesis.…”
Section: Role Of Complex II In Apoptosismentioning
confidence: 99%
See 1 more Smart Citation
“…Both reagents target the SDHA succinate-binding site and equally inhibit the SDH and SQR activities (Brusque et al, 2002;Lemarie et al, 2011). When the tumour-suppressor gene function of complex II subunits was discovered for SDHD, SDHC and SDHB (Baysal et al, 2000;Niemann and Muller, 2000;Astuti et al, 2001), two mechanisms were evoked to explain the oncogenesis process associated with complex II deficiency: (1) the establishment of a pseudo-hypoxic state leading to HIF1a stabilization in tumours through succinate inhibition of the HIF1a prolyl hydroxylase (PHD), which favours the glycolytic pathway and promotes tumour formation (GimenezRoqueplo et al, 2001;Pollard et al, 2005Pollard et al, , 2006Selak et al, 2005;Lehtonen et al, 2007;Cervera et al, 2008) and (2) the long-term generation of sublethal superoxides at the complex II level contributing to either genomic instability and subsequent tumoral development or HIF1a stabilization (Senoo-Matsuda et al, 2001;Ishii et al, 2005;Slane et al, 2006;Guzy et al, 2008). Various key publications subsequently brought to light the possible role of complex II as a proapoptotic sensor, through the production of deleterious high levels of ROS, which could provide a third explanation as to why complex II subunits are disabled in tumourigenesis.…”
Section: Role Of Complex II In Apoptosismentioning
confidence: 99%
“…Moreover, in PGL/PH tumours, which exhibit high levels of HIF1a, this transcription factor was shown to exert a negative regulatory loop on complex II through the downregulation of SDHB expression. This then amplified, in a feed-back loop, the effect leading to further pseudo-hypoxia and HIF1a stabilization (Dahia et al, 2005;Cervera et al, 2008). Moreover, hypoxia was shown to further inhibit complex II activity and generate mitochondrial ROS (Paddenberg et al, 2003;Lluis et al, 2007).…”
mentioning
confidence: 99%
“…Immunocytochemistry was performed using a standard protocol [23]. Cells were incubated with a 1:500 dilution of a-actinin antibody (Sigma-Aldrich) for 2 hours at room temperature (RT), washed again with Tris buffered saline (TBS) and incubated with a 1:100 dilution of fluorescein isothiocyanate-conjugated secondary antibody (Dako Chemicals, Hamburg, Germany, http:// www.dako.com).…”
Section: Immunoblotting and Immunocytochemistrymentioning
confidence: 99%
“…Hypoxia is a characteristic of many malignancies arising from various sites [45] and HIF-1α is a hypoxia responsive factor [16]. Research reported that HIF-1α was upregulated in chronically SDHB-silenced Hep3B cells [24], HIF-1α was overexpressed in SDH-deficient leiomyomas and renal cell cancer (HLRCC) [15]. While there was also report that increased HIF-1α was not associated with loss of SDHB expression on a series of familial and sporadic tumours [11].…”
Section: Discussionmentioning
confidence: 99%
“…The target sequences were as follows: siSucA 5'-GAT TAA GAA TGA AGT TGA CTC-3' [24], siSucC 5'-GCT CAG AGC TGA ACA TAA TT-3' [24]. As a control for silencing, we constructed a negative control (NC) siRNA (5'-UUC UCC GAA CGU GUC ACG UTT-3') that did not affect SDHB expression.…”
Section: Transient Transfection Of Skov3 and A2780 Cells With Sdhb Simentioning
confidence: 99%